40AR/39AR GEOCHRONOLOGY, GEOCHEMICAL AND SR-ND-O ISOTOPIC CHARACTERISTICS OF THE HIGH-MG ULTRAPOTASSIC ROCKS IN LHASA BLOCK OF TIBET: IMPLICATIONS IN THE ONSET TIME AND DEPTH OF NS-STRIKING RIFT SYSTEM - Ding L.; Xu X.; Zhang Q.; Lai Q.; Yue Y.; Cai F. (My University, 2006)
High-Mg ultrapotassic rocks present in the NS-striking rift system of Lhasa Block in Tibetan Plateau. Geochemically these High-Mg ultrapotassic rocks are characterized by relatively high SiO2 (53% ~ 50%), and high K2O (7% ~ 6%), MgO (11% ~ 8%), Cr (500 × 10-6 ~ 400 × 10-6), Ni (400 × 10-6 ~ 260 × 10-6) contents. Isotope data show these volcanic rocks have high86Sr/ Sr36 (0.7265 ~ 0.7199) and low 143Nd/ 144N (0.511844 ~ 0.511769) ratios, and a relatively broad oxygen isotope range (δ18 OVSMOW: 10.4‰ ~ 6.4‰). These geochemical and isotopic characteristics indicate these ultrapotassic rocks are derived from a source of enriched mantle, which were mixed a large quantity component of the subducted India crust. 40Ar/39Ar dating results show these rocks were erupted in 17 ~ 13 Ma. Combined with the relation between the normal faults and volcanic rocks, the normal faults were inferred retaining active intensively in 23 ~ 13 Ma and lasting about 10 Ma, and spreading at a rate of 5.6 ± 3.0 mm/a. The high-Mg ultrapotassic rocks and the rift system are consistent temporally and overlapped spatially, which indicates the high-Mg ultrapotassic rocks are closely correlated with the form and evolution of the rift system in Tibetan Plateau. The break-off of the subducted India crust result in the extension of the lithosphere of Tibetan Plateau. The rifts in Lhasa Block were mainly active in two phases: Firstly, going with the uplift of the Tibetan Plateau (23 ~ 13 Ma), and then occurring gravitational collapse with decrease in elevation of the Tibetan Plateau (13 Ma ~ present).
Keywords: HIGH-MG ULTRAPOTASSIC ROCKS; INCISION DEPTH; LHASA BLOCK; NS-STRIKING RIFT; ONSET AGE